On freedom and the will to adorn : the art of the African American essay - Wall, Cheryl A. (University of North Carolina Press, 2018)
"Beginning with the sermons, orations, and writing of nineteenth-century men and women like Frederick Douglass who laid the foundation for the African American essay, Wall examines the genre's evolution through the Harlem Renaissance. She then turns her attention to four writers she regards as among the most influential essayists of the twentieth century: Baldwin, Ellison, June Jordan, and Alice Walker. She closes the book with a discussion of the status of the essay in the twenty-first century as it shifts its medium from print to digital in the hands of writers like Ta-Nehisi Coates and Brittney Cooper. Wall's beautifully written and insightful book is nothing less than a redefinition of how we understand the genres of African American literature."--Publisher's description